Prosody, syntax, and pragmatics: insubordination in spoken Brazilian Portuguese - Bossaglia, Giulia; Mello, Heliana; Raso, Tommaso (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2017: Anais do XI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2017)
In this paper, we approach the phenomenon of insubordination in spoken Brazilian Portuguese through data on adverbial clauses extracted from the C-ORAL-BRASIL corpus [Raso and Mello 2012]. Differently from the traditional conception of insubordination [Evans 2007], we propose a synchronic view, strongly based on the analysis of the prosody/pragmatics interface in spoken language. We show that in spoken Brazilian Portuguese formally dependent syntactic structures can acquire pragmatic autonomy by virtue of specific prosodic patterns conveying certain informational values.